Burden, access, and disparities in kidney disease - Crews, Deidra C; Bello, Aminu K; Saadi, Gamal; Steering Committee, World Kidney Day (African Journal of Nephrology, 2019)
This World Kidney Day 2019 article is being published in Kidney International and reprinted concurrently in several journals. The articles cover identical concepts and wording, but vary in minor stylistic and spelling changes, detail, and length of manuscript in keeping with each journal’s style. Any of these versions may be used in citing this article. Note that all authors contributed equally to the conception, preparation, and editing of the manuscript.